The effects of acute exercise on emotional pattern separation in adolescents and young adults - Lise Jennen; Victor Mazereel; Davy Vancampfort; Zhiling Qiao; Kristof Vansteelandt; Patrick Dupont; Aleksandra Lecei; Ruud van Winkel (NeuroImage)
Acute exercise has been associated with cognitive improvements, particularly in memory processes linked to the hippocampus, such as the ability to discriminate between similar stimuli, called hippocampal pattern separation. This can be assessed behaviorally with a mnemonic discrimination task and neurally with functional magnetic resonance imaging (fMRI). Additionally, previous research has shown an emotional modulatory effect on pattern separation, involving the amygdala. In this randomized between-subject study, we investigated whether a 10-minute bout of moderate-intensity exercise, compared to rest, could enhance pattern separation of neutral and emotional images in a group of healthy adolescents and young adults (n=53). Our results showed no significant effects of exercise on either mnemonic discrimination performance or neural activity in the hippocampus and amygdala. Additionally, arterial spin labeling (ASL) confirmed that there were no significant differences in cerebral blood flow between exercise and rest. We did observe worse discrimination for images with a higher similarity level and worse discrimination for highly similar positive images compared to negative and neutral images. However, there were no significant correlations between behavioral outcomes and neural activity. Exploratory analysis revealed a neural signal consistent with pattern completion in the bilateral CA1 and left CA3, but no evidence of pattern separation. Future studies should optimize the exercise characteristics necessary to robustly enhance pattern separation.